LEARNING TO TEACH FOR NEW ENGLISH TEACHERS - Ningrum, Ary Setya Budhi (Pusat Pengembangan Bahasa IAIN Tulungagung, 2010)
The role of English as an international language is unavoidable force people to learn it in order to make them not to be left behind with others. Learning English in Indonesia, of course, needs a teacher as it is a foreign language here. This phenomenon make a lot of people want to be an English teacher as their job. However, to be a good teacher is not easy. One of the important things that someone should occupy is about the teaching method. Therefore, this paper tries to give a brief summary of well-known teaching methods and approaches in practice today for new teachers as a starting point from which they can modify their practice.